Microstructure-toughness relationship in the simulated CGHAZ of V-N microalloyed X80 pipeline steel. Issue 12 (13th August 2021) - Wang, Ming-Ming; Gao, Xiu-Hua; Song, Li-Ying; Zhu, Cheng-Lin; Misra, R. D. K.; Du, Lin-Xiu
Abstract : The microstructure evolution, hardness and impact toughness in the simulated coarse-grained heat-affected zone (CGHAZ) of a V-N microalloyed X80 pipeline steel were studied. The results indicated that the microstructure mainly consisted of bainitic ferrite, acicular ferrite and granular bainite. The area fraction and size of M/A constituents were increased with increasing heat input. As heat input increased from 15 to 60 kJ cm −1, the hardness gradually decreased from 301 to 243 HV, and impact energy decreased from 284 to 33 J. Hardness in the CGHAZ was not sensitive to heat input. When the heat input exceeded 30 kJ cm −1, the formation of coarse granular bainite and large-sized blocky M/A constituents resulted in the deterioration of impact toughness.